Dual catastrophe of COVID-19: Massive pulmonary embolism and stroke in a previously healthy young patient: A case report. Issue 5 (May 2021) - AlSheef, Mohammed; Zaidi, Abdul Rehman Z.; Abonab, Majid; Obaid, Mona; Bawazir, Khalid; Zaidi, Syed Ziauddin A.; Kullab, Ghaydaa J.; Alawfi, Sultan; Enani, Mushira
Abstract: We are reporting a 45-year-old woman with COVID-19 who presented to the Emergency Department with a transient loss of consciousness and was found to have a massive pulmonary embolism and an acute stroke. To our knowledge, this is the first reported case that calls for attention to the importance of vigilance for such a catastrophic presentation of COVID-19.